The Effectiveness of Death Penalty as an Effort to Counter Serious Crimes: A Literature Review - Ferdinanta, Ach. Safi’ie; Saputra, Rio; Darmawan, Didit (Bulletin of Science, Technology and Society, 2024)
This study aims to explore the effectiveness of the death penalty as a legal instrument in tackling serious crimes in Indonesia, including corruption, narcotics, and terrorism. The literature review shows that the death penalty has potential as a deterrence tool, but its effectiveness is often affected by inconsistencies in law enforcement, lack of transparency in the judicial process, and criticism from a human rights perspective. On the other hand, public support for the death penalty reflects the desire for strict law enforcement. This study recommends regulatory revisions, strengthening judicial transparency, and penal alternatives as steps to improve the effectiveness of the death penalty in Indonesia's criminal law system.